EFEKTIVITAS PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMK NEGERI 1 PAREPARE - Muhammad Jufri (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This article discusses about the Effectiveness of Learning Student Team Achievement Division in Improving Student Learning Outcomes in SMK Negeri 1 Parpare. The importance of this research is done because of the essence of learning trough student team achievement division and the implementation steps have not been done on the research object. The level of learning decided of student still need to be maximized to achieve the minimum completion criteria established by the school. The objective of the research is to know the form of implementation and effectiveness of learning trough Student Team Achievement Division in improving the outcomes (result) of learning Islamic Religion Education for the eleventh grade on SMK Negeri 1 Parepare.The research setting used in this research is a classroom action research which was conducted cyclically with experimental approach. The subjects of this research are the eleventh grade (class) on SMK Negeri 1 Parepare and the numbers of the subjects are 25 student. The method of data collection as research instrument is test, participant observation sheet, and documentation, the data analysis technique used frequency distribution analysis.The research result found that: (1) the implementation of learning student team achievement division has a positive impact on the cooperation among student which is shown by the responsibility of the students in the group, in the learning process by using the learning student team achievement division that is done in cyclical technique student activeness has improved better than using lecturing method. (2) The results of learning Islamic Religion Education have been increased after using the learning student team achievement division. This can be shown from the average score of the students test, the average of pre test is 70,4; in the first cycle the score average of the post test increased up to 85,80; and in the final test (post test) of the second cycle the score average increased up to 96,60. As cocnclusion, Student Team Achievement Division (STAD) as learning strategy is effective to improve the students learning outcomes of the eleventh grade of SMK Negeri 1 Parepare.